Upregulation of MKP-7 in response to rosiglitazone treatment ameliorates lipopolysaccharide-induced destabilization of SIRT1 by inactivating JNK. (December 2016) - Hwang, Jung Seok; Ham, Sun Ah; Yoo, Taesik; Lee, Won Jin; Paek, Kyung Shin; Kim, Jae-Hwan; Lee, Chi-Ho; Seo, Han Geuk
Graphical abstract: Abstract: Silent mating type information regulation 2 homolog 1 (SIRT1), a NAD-dependent deacetylase, mediates cellular processes involved in gene silencing and aging. The regulation of lifespan by SIRT1 has been extensively investigated, but less is known about the mechanisms associated with its cellular turnover during inflammatory responses. In this study, we found that peroxisome proliferator-activated receptor (PPAR) γ is associated with SIRT1 stability in murine macrophage RAW 264.7 cells exposed to lipopolysaccharide (LPS). Activation of PPARγ by rosiglitazone, a specific ligand of PPARγ, rescues LPS-induced destabilization of SIRT1, with a concomitant decrease in phosphorylation of residue Ser-46, which is targeted by JNK-1 to promote proteasome-mediated degradation of SIRT1. The rosiglitazone-mediated increase in SIRT1 stability is accompanied by upregulation of mitogen-activated protein kinase phosphatase (MKP)-7, a JNK-specific phosphatase. These effects are significantly influenced by ablation or ectopic expression of PPARγ, indicating that PPARγ is directly involved in the regulation of SIRT1 stability. Furthermore, gain of MKP-7 function mimicked the effect of rosiglitazone on LPS-induced destabilization and ubiquitination of SIRT1. These results indicate that PPARγ-dependent upregulation of MKP-7 improves the stability of SIRT1 by inactivating JNK during inflammatory responses of LPS-activated macrophages.